SOSIALISASI AKUNTANSI PRAKTIS: MENUMBUHKAN JIWA KEWIRAUSAHAAN DI KALANGAN SISWA SISWI SMA ISLAHIL ATHFAL RUMAK - Luh Utami; Widiya Pratiwi; Dina Yuliartika (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
ABSTRACT The community service activity entitled "Socialization of Practical Accounting: Growing the Spirit of Entrepreneurship among Students of Islahil Athfal Rumak High School" aims to provide students with a basic understanding of accounting and entrepreneurship. In the era of globalization and digital economic development, the ability to manage finances is an important skill for individuals, including students. Through this socialization, students are taught about recording simple financial transactions, capital management, and the concept of profit and loss in the context of small businesses. The method used was participatory with an interactive approach that proved effective in improving students' understanding. The results of the pre-test and post-test analysis showed a significant increase in participants' knowledge after participating in this activity. It is hoped that similar activities can be extended to other schools to improve financial literacy among students.